Adr Caused Byanti-Snake Venom a Case Report Highlighting the Pathophysiology, Prevention, and It’s Management - Shivani Chandrashekhar Bedarkar; Avishkar Hanamantrao Agarkhed (International Journal of Toxins and Toxics, 2024)
Even in situations where it wasn't necessary, antivenom research was applied to snake bite cases. In order to improve their level of understanding, primary practitioners should receive training on handling envenomation situations as well as current recommendations and references. In cases of snake bites, antivenom must be delivered according to applicable systemic and original indications.More than ten percent of cases with admitted ASV experience some sort of reaction, ranging from a minor urticarial rash to a serious anaphylactic reaction. While antivenoms are the first line of treatment in situations of life-threatening envenomation, especially snake sucks, they also result in serious adverse medication reactions. Asia is home to many different species of snakes, and one of the biggest health risks is hemotoxic snake envenomation. Because of resource limitations, the standard diagnostic procedure calls for a 20-minute whole blood clotting time (20WBCT). Antisnake venom (ASV) must be administered in cases of systemic envenomation, which is characterized by bleeding problems or an extended clotting time. This case report describes a patient who needed two doses of ASV at first, but whose clotting time eventually recovered to normal. The case report that is being presented highlights even more the variation in the way that patients react to antivenom, illuminating the complexities of treatment and the need for close observation. The goal of this all-inclusive strategy is to improve practitioners' proficiency in handling cases of snake envenomation, reducing risks, and improving patient outcomes.
Keywords: Anaphylaxis; Antivenom; Elixir responses; Envenoming; snakebite